Isolation and Analysis of Microplastics in Vaname Shrimp (Litopenaeus vannamei Boone, 1931) at Tanjung Luar Fish Landing Base, East Lombok Regency - Adawiyah, Rabiatul; Prasedya, Eka Sunarwidhi; Candri, Dining Aidil (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2024)
Microplastics are plastic debris resulting from the fragmentation process that has a size less than <5 mm. Microplastic contamination in marine waters can have a direct impact on the ecosystem and digestive system of aquatic biota, and is dangerous for humans if consumed because it is toxic. This study aims to determine the abundance and characteristics of microplastics in Vaname shrimp (Boone, 1931) collected by Tanjung Luar Fish Landing Base (PPI), East Lombok Regency, Indonesia. Vaname shrimp samples were taken using the Random Sampling method obtained from fishermen at the Tanjung Luar Fish Landing Base, analyzing the abundance and characteristics of microplastics with 10% KOH. The results showed that the abundance of microplastics obtained was 37 particles with the most accumulated type of microplastics, namely the fiber form of 22 particles/gram with the most dominant color, namely black as much as 57%. There are 3 forms of microplastics found in vaname shrimp meat (Littopenaeus vannamei), namely fiber 22 particles, fragments 11 particles and filaments 4 particles. Black color as much as 57%, followed by clear color as much as 27%, yellow as much as 11%, and blue as much as 5%.